Non-linear Incentives, Worker Productivity, and Firm Profits: Evidence from a Quasi-Experiment - Richard B. Freeman; Wei Huang; Teng Li (Institute of Labor Economics (IZA), 2021)
Using administrative data from a major Chinese insurance firm that raised its sales targets and rewards for insurance agents in a highly non-linear incentive system, we find that the improvement in productivity far outweighed the costs associated with bunching distortions and other gaming behaviors. Labor turnover decreased, which suggests that the extra pay for workers exceeded the non-pecuniary cost of extra effort by workers, and thus improved their well-being. The firm gained about two-thirds of the higher net output, making the reform profitable. Analysis of non-linear incentive systems should accordingly focus more on the productivity-enhancing than on the distortionary effects.
Keywords: J33; M52; 330; non-linear incentives; insurance commission; strategic gaming behavior; productivity; turnover rates